PELAYANAN KEAGAMAAN DI KAWASAN PERBATASAN ENTIKONG DAN SEKAYAM, PROVINSI KALIMANTAN BARAT - Fakhruddin Fakhruddin; M. Ishom M. Ishom (Harmoni, 2017)
Entikong and Sekayam are two sub-districts in Sanggau directly adjacent to the territory of Malaysia. Both sub-districts have been designated as priority sites of border areas development. Religious services in the border areas are still far from expectations and do not reflect the principle of satisfactory service community as stipulated in Ministrial Decree PAN No. 63/ KEP/M.PAN/7/2003. It is caused by many factors. So, related to the functions of implementation of development in the religious field, the Ministry of Religious Affair has adopted program of ibadah (religious worship). General religious services are part of the public services, i.e all activities undertaken by public service providers as effort to meet the needs of service recipients, as well as in order to implement the statutory provisions. The main basis of religious services in Indonesia are the first principle of Pancasila and Article 27 of the 1945 Constitution. Religious services in Indonesia can be conducted by public service providers, both government and socio-civil elements. It is unique, because despite Indonesia is not a religious state, the great role of religion in the history of the state formation can not be denied. Therefore, Indonesia government does not let the religious affair to be in the private domain but it is involved in conducting religious services in accordance with statutory provisions. The scope of religious services conducted by state according to law include: Islamic marriage, zakat/ infaq/charity/endowments, pilgrimage, religious education, and so forth. Out of those aforementioned, religious services is submitted to the social and religious institutions.